'Compassionate use' protocol for auditory brainstem implantation in neurofibromatosis type 2: Early House Ear Institute experience. (2nd January 2017) - Roberts, Daniel S.; Slattery, William H.; Chen, Brian S.; Otto, Steve R.; Schwartz, Marc S.; Lekovic, Gregory P.
Abstract : Objective: To report the preliminary outcomes of auditory brainstem implantation (ABI) under a compassionate use protocol for two ABI devices that are not approved by the US Food and Drug Administration. Methods: A retrospective review was performed of neurofibromatosis type 2 (NF2) patients who underwent microsurgery for vestibular schwannoma (VS) and placement of either the Cochlear ABI541 or Med-El Synchrony ABIs. Peri-operative and device- related complications were reviewed. Audiometric performance was also evaluated. Results: Seven patients received either the Cochlear ABI541 (6) or the Med-El Synchrony ABI (1) after the resection of VS. No device or patient-related complications occurred to date. Surgical times and early audiological performance are similar to our previous experience with the Cochlear ABI24 device. Conclusions: Early experience with the Cochlear ABI541 and Med-El Synchrony ABI devices under a compassionate use protocol suggest that both devices are safe with comparable utility to the Cochlear ABI24 device.